PENGEMBANGAN TEKO SENJA (SENSOR JARAK) SEBAGAI ALAT BANTU TUNANETRA - adi, nugroho prasetya; Latifah, Lutfatul; Harti, Harti (AL-QALAM: JURNAL ILMU KEPENDIDIKAN, 2022)
The purpose of this research is to create SENJA (Proximity Sensor) teapot to make it easier for the blind. The type of research used in this research is the experimental method. Experimental research method is a quantitative research method used to determine the effect of the independent variable (treatment) on the dependent variable (outcome) under controlled conditions. This study uses several components such as proximity sensors, water pumps, and water level alarms which are arranged in such a way as to form the circuit. This tool applies the concept of physics, namely Toricelli's Theorem. The results of this study are to determine the effect of the sensor response time with the distance of the hole to the water surface based on the concept of toricelli theory, and it is stated that the deeper the hole to the water surface, the faster the sensor response to remove water from the teapot. The percentage of error in this study is less than 5%. This proves that the error or error of the tool is very minimal. So that this tool can be declared valid.